ADA APA DENGAN PONDOK WISATA? SELUK BELUK KEBERADAAN PONDOK WISATA DI UBUD - Pratiwi, Wahyuni Berlian Dwi; Sukana, I Made (JURNAL DESTINASI PARIWISATA; Vol 4 No 1 (2016): VOL 4, NO 1 (2016): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2016.v04.i01.p07, 2016)
Abstract Along with the increasing number of tourists who visited Ubud, the growth of facilities that provided for tourists to stay in Ubud is also growing rapidly. This is evidenced by the proliferation of the existing lodges. So this study evaluated the existence of lodges in Ubud today . In determining the lodges to be studied, the technique that used is random technique which is assisted by random.org program. The method of observation and in-depth interviews is used for collecting data whereas descriptive qualitative is used for analyzed the data. The finding identify that the existence lodges in Ubud preceded by a lodge named Tjanderi Homestay. Until the year 2012 the number of  lodge s in Ubud has been increased significantly by as much as 445 lodge s scattered throughout the Ubud district. Most of that lodges were built in the teba (backyard). In promote the ir lodge s , the owners use conventional networks such as information mouth to mouth, guide networking and networking among local lodge owners. Traditional marketing is combined with modern networks such as Global Distribution System and website. Beside of that, the competition in terms of facilities, marketing and the competition in terms of price are also still be found.
Keywords: Lodges, Existenc